2021
DOI: 10.3390/biomedicines9091140
|View full text |Cite
|
Sign up to set email alerts
|

Glycomacropeptide for Management of Insulin Resistance and Liver Metabolic Perturbations

Abstract: Background and Aims: The increasing prevalence and absence of effective global treatment for metabolic syndrome (MetS) are alarming given the potential progression to severe non-communicable disorders such as type 2 diabetes and nonalcoholic fatty liver disease. The purpose of this study was to investigate the regulatory role of glycomacropeptide (GMP), a powerful milk peptide, in insulin resistance and liver dysmetabolism, two central MetS conditions. Materials and Methods: C57BL/6 male mice were fed a chow (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Inflammation, oxidative stress, and dysregulated autophagy are common features in noncommunicable diseases and may be key targets for the development of novel therapeutic strategies [ 43 ]. Previous studies have shown that GMP exerts immunomodulatory, anti-oxidative, and anti-inflammatory activities in rodent models of noncommunicable diseases in which macrophage activation is related with pathophysiology [ 28 , 29 , 30 , 31 ]. However, the direct effect of GMP on human macrophage activation had not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation, oxidative stress, and dysregulated autophagy are common features in noncommunicable diseases and may be key targets for the development of novel therapeutic strategies [ 43 ]. Previous studies have shown that GMP exerts immunomodulatory, anti-oxidative, and anti-inflammatory activities in rodent models of noncommunicable diseases in which macrophage activation is related with pathophysiology [ 28 , 29 , 30 , 31 ]. However, the direct effect of GMP on human macrophage activation had not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…GMP was found to exert immunoregulatory, anti-inflammatory, and antioxidant activities in models of allergy and intestinal inflammatory diseases [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In relation to metabolic diseases, GMP intake has shown promising effects on the prevention of insulin resistance and liver dysmetabolism in mice receiving a high-fat and high-sucrose diet [ 28 ]. In a streptozotocin-induced and high-fat diet-induced diabetic mouse model, a papain hydrolyzed GMP showed antidiabetic effects [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our laboratory highlighted the ability of glycomacropeptide (GMP) to counteract oxidative stress (OxS) and inflammation in intestinal Caco-2/15 cells [ 12 ], along with the amelioration of some aspects of MetS, such as insulin resistance (IR). In a subsequent study, we validated these findings using a murine model exposed to a high-fat, high-sucrose diet [ 13 ]. Interestingly, the administration of GMP to high-fat, high-sucrose diet-fed mice resulted in significant attenuation of IR, which is central to MetS pathogenesis.…”
Section: Introductionmentioning
confidence: 86%
“…An animal study by Sauvé M. F. investigated the impact of glycomacropeptide on insulin resistance and hepatic dysmetabolism. The authors concluded that glycomacropeptide supplementation for 12 weeks exerted important antioxidant and anti-inflammatory actions and improved insulin sensitivity [ 15 ].…”
mentioning
confidence: 99%